2015
DOI: 10.1210/en.2014-1653
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acid Receptor GPR120 Is Highly Expressed in Enteroendocrine K Cells of the Upper Small Intestine and Has a Critical Role in GIP Secretion After Fat Ingestion

Abstract: Gastric inhibitory polypeptide (GIP) is an incretin secreted from enteroendocrine K cells in response to meal ingestion. Recently free fatty acid receptor G protein-coupled receptor (GPR) 120 was identified as a lipid sensor involved in glucagon-like peptide-1 secretion. However, Gpr 120 gene expression and its role in K cells remain unclear, partly due to difficulties in separation of K cells from other intestinal epithelial cells. In this study, we purified K cells using GIP-green fluorescent protein (GFP) k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 48 publications
2
75
0
Order By: Relevance
“…300,313,314 Detailed examination of FFA4 expression in the intestine indicated that FFA4 is expressed by the enteroendocrine cells on each of the L, K, and I cells. 125,300,315 At least one study has also shown more widespread expression of FFA4 within the intestine, extending to the intestinal epithelial cells in addition to the enteroendocrine cells. 316 Interestingly, several factors seem to regulate FFA4 expression in the intestine, and these may be species and/or strain dependent.…”
Section: Expression Of Ffa4mentioning
confidence: 99%
“…300,313,314 Detailed examination of FFA4 expression in the intestine indicated that FFA4 is expressed by the enteroendocrine cells on each of the L, K, and I cells. 125,300,315 At least one study has also shown more widespread expression of FFA4 within the intestine, extending to the intestinal epithelial cells in addition to the enteroendocrine cells. 316 Interestingly, several factors seem to regulate FFA4 expression in the intestine, and these may be species and/or strain dependent.…”
Section: Expression Of Ffa4mentioning
confidence: 99%
“…Indeed, the FFA1 agonist fasiglifam entered phase III clinical trials; although it was clearly able to regulate glycemia and to produce clinically relevant lowering of hemoglobin A1c levels in patients with type 2 diabetes Poitout, 2013, 2015;Kaku et al, 2015), it was withdrawn from further trials because of concerns of possible liver toxicity. Although FFA4 is expressed in the pancreas (Stone et al, 2014;Suckow et al, 2014), where it may play roles in the regulation of glucagon production (Suckow et al, 2014), it is also expressed in various enteroendocrine cells (Parker et al, 2009;Iwasaki et al, 2015;Liu et al, 2015), adipocytes (Oh et al, 2010(Oh et al, , 2014Liu et al, 2015) and macrophages (Oh et al, 2010(Oh et al, , 2014Im, 2015;Liu et al, 2015). Potential combinations of effects on the release of incretins and/or satiety-regulating hormones in the gut, differentiation of and uptake of glucose by adipocytes, and control of the release of inflammatory mediators by macrophages have suggested that FFA4 might also be a useful therapeutic target to modulate insulin resistance and glucose homeostasis Oh et al, 2014;Liu et al, 2015;Milligan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CD36 and GPR40 appear to contribute the main part of FA-induced cholecystokinin release during fat absorption. Both GPR40 and GPR120 mediate release of the incretins, GLP-1 and GIP, in response to FAs (9,44,45), whereas CD36 does not appear to be directly involved in this process. However, in the CD36-null mouse, secretion of both GIP and GLP-1 is enhanced as a result of the delayed fat absorption (S Sundaresan, F Nassir, and NA Abumrad, unpublished results, 2015) and of more dietary fat that reaches GPR40 and GPR120 in the ileum where both receptors are well expressed (9,46).…”
Section: Role Of Cd36 In Intestinal Fa Sensingmentioning
confidence: 97%